Municipal education systems in Rio Grande do Sul, Brazil: a close look at the teacher - Flávia Obino Corrêa Werle; Carolina Obino Corrêa; Alenis Cleusa de Andrade (Universidade Federal de Santa Catarina, 2009)
This article discusses municipal educational policies focusing on the theme of education and emphasis on teaching. It analyzes municipal educational systems (MES) in Rio Grande do Sul (RS) and the importance of decentralization and articulation of municipal education in the form of educational systems. The work is organized in five parts. The first presents a theoretical debate about political autonomy of local governments based on Giddens (1991, 2002). The second analyses educational policies considering laws governing MES within Brazil's constitutional framework. The third presents the emphasis on teaching in Brazilian legislation. The fourth presents methodology, while the fifth analyzes municipal laws governing municipal educational systems in Rio Grande do Sul, presenting their characteristics concerning the importance of the teacher and school directors, teachers aides and other employees who work in municipal education. It reaffirms the importance of the political autonomy of local governments.